Rumble - Hopkins, Ellen (New York : Margaret K. McElderry Books, 2014)
Eighteen-year-old Matt's atheism is tested when, after a horrific accident of his own making that plunges him into a dark, quiet place, he hears a voice that calls everything he has ever disbelieved into question.
Keywords: Novels in verse; Atheism -- Fiction; Family problems -- Fiction; Dating (Social customs) -- Fiction; High schools -- Fiction; Schools -- Fiction; Grief -- Fiction